Wandering Son. Volume seven - Shimura, Takako, 1973- (Fantagraphics Books, 2014)
After the success of their gender-bending rendition of "Romeo and Juliet," Nitori-kun, the boy who wants to be a girl, and Chiba-san, the girl who is crushing on him, are scouted by a theater company, leaving Takatsuki-san, the girl who wants to be a boy, jealous, as she knows Nitori is crushing on her.